2004
DOI: 10.1097/00001756-200403010-00028
|View full text |Cite
|
Sign up to set email alerts
|

Cortical activity associated with auditory hallucinations

Abstract: Auditory hallucinations are one the most enigmatic and hampering symptoms associated with schizophrenia. Non-invasive functional imaging techniques have begun to delineate the underlying neuronal basis. We investigated the spontaneous magnetoencephalographic activity in a 33-year-old male schizophrenic patient and compared the results to those obtained from 13 healthy controls. Despite current neuroleptic medication (clozapine) the patient was still suffering from auditory hallucinations. Using the dipole dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 23 publications
4
39
0
1
Order By: Relevance
“…However, as they note in their discussions, the correlation between γ PLF and hallucinations was found on a measure reflecting the lifetime history of hallucinations in patients who were not hallucinating during the study. Actively hallucinating patients have demonstrated high amplitude β/γ oscillations in the appropriate sensory cortex, 45,46 and there have been other studies indicating positive correlations between γ and positive symptoms. 47,48 The contrast between the finding by Spencer and colleagues 5 of a correlation between γ PLF and history of hallucinations and those from studies that reported increased amplitude in patients actively experiencing hallucinations may suggest that the γ PLF reflects a proneness to hallucinatory experiences when there is ineffective dopaminergic antagonism to dampen γ oscillations.…”
Section: Effects Of Dexamphetamine On the Assrmentioning
confidence: 98%
“…However, as they note in their discussions, the correlation between γ PLF and hallucinations was found on a measure reflecting the lifetime history of hallucinations in patients who were not hallucinating during the study. Actively hallucinating patients have demonstrated high amplitude β/γ oscillations in the appropriate sensory cortex, 45,46 and there have been other studies indicating positive correlations between γ and positive symptoms. 47,48 The contrast between the finding by Spencer and colleagues 5 of a correlation between γ PLF and history of hallucinations and those from studies that reported increased amplitude in patients actively experiencing hallucinations may suggest that the γ PLF reflects a proneness to hallucinatory experiences when there is ineffective dopaminergic antagonism to dampen γ oscillations.…”
Section: Effects Of Dexamphetamine On the Assrmentioning
confidence: 98%
“…Within the context of MEG investigations in schizophrenic patients with auditory hallucinations, different results were found especially with regard to dipole distribution within the slow and fast frequency bands. While Ropohl et al [10] described an increase in fast dipole activity over the left temporal lobe during auditory hallucinations, investigations by Wienbruch et al [5] showed a left temporal increase in slow activity in schizophrenic patients with auditory hallucinations compared with healthy controls. On the basis of the variation in results, the inclusion of psychopathological differentiation appears to be decisive.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, alterations of white matter fiber tracts were found in the left hemisphere in patients with auditory hallucinations [8] . In MEG studies, hallucinating participants demonstrated a network of different cortical activations, including bilateral auditory cortex, left limbic regions, and right medial and right prefrontal cortex [1,5,9,10] . Other recent functional neuroimaging studies have confirmed the pattern of distributed structural abnormalities specific to hallucinations [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…With these inconsistencies, the registration of the effects of rTMS on biological activity is an important addition to such trials. There are some indications that electroencephalographic (EEG) ␤ -frequency band activity is increased in the left temporal lobe during AH [19,20] .…”
mentioning
confidence: 99%